A fireproof composite board based on magnesium oxysulfide and preparation method thereof

By combining modified magnesium sulfide cement slurry and hierarchical structure, the brittleness and water resistance of magnesium sulfide cement materials in external forces and humid environments are solved, and higher flexural strength, water resistance and fire resistance are achieved.

CN119241198BActive Publication Date: 2025-04-15JIANGSU JINPENG FIREPROOF BOARD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411270522.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-04-15
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

As a brittle material, existing magnesium sulfhydryl cement is prone to cracking under external force and has poor water resistance, which limits its use in applications where waterproofing is required.

Method used

Modified magnesium sulfate cement slurry is prepared by mixing lightly flammable magnesium oxide and magnesium sulfate aqueous solution and adding modifiers, composite aerogels, active blends and foaming agents, and combined with the hierarchical structure of alkali-resistant glass fiber mesh fabric and non-woven fabrics, and curing treatment is carried out to improve the performance of the material.

Benefits of technology

It significantly improves the flexural strength, water resistance and fire resistance of magnesium sulfhydryl material, extends its service life, and improves its applicability in different application environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of composite panels, and specifically to a fireproof composite panel based on magnesium oxysulfide and a preparation method thereof. The present invention obtains a modified magnesium oxysulfide cement slurry by uniformly mixing light-burned magnesium oxide and an aqueous solution of magnesium sulfate, adding a modifier, a composite aerogel, an active admixture and a foaming agent and mixing them uniformly; laying a layer of non-woven fabric and a layer of alkali-resistant glass fiber mesh cloth on the template in sequence, pouring the modified magnesium oxysulfide cement slurry, and then laying a layer of alkali-resistant glass fiber mesh cloth and a layer of non-woven fabric in sequence; performing primary curing and secondary curing to obtain a fireproof composite panel. The fireproof composite panel prepared by the present invention not only has excellent fireproof performance, can effectively prevent flame propagation and heat conduction, but also has good mechanical strength and water resistance, meeting the high requirements of modern buildings for fire prevention and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite boards, in particular to a fireproof composite board based on magnesium oxysulfide and a preparation method thereof. Background Art

[0002] As the demand for fireproof materials in the construction industry continues to increase, fireproof composite panels, as an important building material, have gradually attracted widespread attention. Magnesium oxysulfate (MOS) cement is an air-hardening cement slurry composed of a ternary system of MgO-MgSO4-H2O. It has the characteristics of being lightweight, high temperature resistant, easy to prepare, and green and environmentally friendly. Therefore, it has been used in fireproof door core panels, exterior wall insulation panels and other fields.

[0003] However, as a brittle material, magnesium oxysulfate cement is prone to brittle cracking under external forces. This characteristic makes it show poor durability in practical applications, especially in environments with impact or vibration. At the same time, magnesium oxysulfate cement has poor water resistance and is easily affected by humid environments, resulting in reduced strength and stability of the material. This limits its use in some applications that require waterproofing.

[0004] Therefore, we propose a fireproof composite board based on magnesium oxysulfide and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a fireproof composite board based on magnesium oxysulfide and a preparation method thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a fireproof composite board based on magnesium oxysulfide comprises the following steps:

[0008] Step S1: light-burned magnesium oxide and magnesium sulfate aqueous solution are mixed evenly, and a modifier, a composite aerogel, an active admixture and a foaming agent are added and mixed evenly to obtain a modified magnesium oxysulfate cement slurry;

[0009] Step S2: laying a layer of non-woven fabric and a layer of alkali-resistant glass fiber mesh cloth on the template in sequence, pouring modified magnesium oxysulfate cement slurry, and then laying a layer of alkali-resistant glass fiber mesh cloth and a layer of non-woven fabric in sequence; performing primary curing and secondary curing to obtain a fireproof composite board.

[0010] Furthermore, the modified magnesium oxysulfate cement slurry includes the following components by weight: 20-45 parts of light-burned magnesium oxide, 25-50 parts of magnesium sulfate aqueous solution, 5-15 parts of composite aerogel, 15-25 parts of active admixture, 0.1-0.5 parts of foaming agent, and 0.1-3.0 parts of modifier.

[0011] Furthermore, the magnesium sulfate aqueous solution has a density of 1.2 to 1.3 g / cm 3 of magnesium sulfate aqueous solution.

[0012] Furthermore, the preparation method of the composite aerogel is as follows:

[0013] Step (1): mixing a graphene oxide aqueous solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, ultrasonically treating for 30 to 60 minutes, adding a mixed solution of oleylamine, ethanol and deionized water, continuing the ultrasonic treatment for 2 to 3 hours, stirring for 22 to 24 hours, centrifuging, filtering and drying to obtain graphene oxide containing double bonds;

[0014] Step (2): uniformly mixing the double-bond-containing graphene oxide, a flame retardant and a photoinitiator, and irradiating the mixture with ultraviolet light to obtain modified graphene oxide;

[0015] Step (3): evenly mix the carboxymethyl chitosan aqueous solution, modified graphene oxide, nanocellulose and hydroxyapatite nanowires, perform ultrasonic treatment for 1 to 2 hours, add glutaraldehyde and stir evenly, and stand for 3 to 5 hours to obtain a composite hydrogel; and pre-freeze and freeze-dry the composite hydrogel to obtain a composite aerogel.

[0016] Furthermore, in the step (1), the mass ratio of the graphene oxide aqueous solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(0.012-0.015):(0.010-0.012), and the concentration of the graphene oxide aqueous solution is 10 mg / mL.

[0017] Furthermore, in step (1), the mass ratio of oleylamine to ethanol and deionized water is 1:(15-20):(10-20), and the mass of oleylamine is 3-5% of the mass of the graphene oxide aqueous solution.

[0018] Furthermore, in step (2), the mass ratio of the double-bond graphene oxide, the flame retardant and the photoinitiator is 1:(2-4):(0.3-0.5).

[0019] Furthermore, the photoinitiator is 2-hydroxy-2-methylpropiophenone.

[0020] Furthermore, in step (2), the process conditions of ultraviolet irradiation are: irradiation wavelength 360-400nm, irradiation time 0.5-2.0h, irradiation intensity 20-35mW / cm 2 .

[0021] Furthermore, the preparation method of the flame retardant is as follows:

[0022] Step A: Mix melamine and pyridine evenly, heat to 40-50° C., introduce nitrogen, add thioglycolic acid and dicyclohexylcarbodiimide and mix evenly, heat to 60-70° C., keep warm for 1-2 hours, filter, distill under reduced pressure, and dry to obtain modified melamine;

[0023] Step B: 4-hydroxyphenylboronic acid and tetrahydrofuran are mixed evenly, and phenylphosphoryl dichloride, dibutyltin oxide and triethylamine are added under ice bath conditions, and the reaction is continued for 2 to 4 hours, and the reaction is continued for 8 to 10 hours at room temperature, and an intermediate is obtained after precipitation, filtration, washing and drying;

[0024] Step C: Under nitrogen protection, the modified melamine, the intermediate, toluene and triethylamine are mixed uniformly, reacted at 65-75° C. for 2-4 hours, and the flame retardant is obtained after filtering, washing and drying.

[0025] In the above technical scheme, the carboxyl group of thioglycolic acid and the amino group of melamine undergo an amidation reaction, and the reaction can be carried out under mild conditions with the help of a dehydrating agent. By controlling the melamine to be slightly excessive, only one amino group on the melamine participates in the reaction, thereby obtaining modified melamine. Then, by controlling the phenylphosphoryl chloride to be slightly excessive, a -Cl in the phenylphosphoryl chloride reacts with a hydroxyl group in 4-hydroxyphenylboric acid, and triethylamine removes hydrogen chloride generated by the reaction to obtain an intermediate. Finally, the remaining -Cl in the phenylphosphoryl chloride reacts with an amino group in the modified melamine to obtain a flame retardant containing N, P, and B elements.

[0026] Furthermore, in step A, the mass ratio of melamine, pyridine, thioglycolic acid and dicyclohexylcarbodiimide is 1: (6.5-7.0): (0.6-0.7): (1.3-1.5).

[0027] Furthermore, in step B, the mass ratio of 4-hydroxyphenylboric acid, tetrahydrofuran, phenylphosphinoyl dichloride, dibutyltin oxide and triethylamine is 1: (5-10): (1.5-1.6): (0.01-0.03): (0.8-1.0).

[0028] Furthermore, in step C, the mass ratio of modified melamine, intermediate, toluene and triethylamine is 1:(1.4-1.5):(5-7):(0.8-1.0).

[0029] Furthermore, in step (3), the mass ratio of carboxymethyl chitosan, modified graphene oxide, nanocellulose and hydroxyapatite nanowires is 1: (0.2-0.5): (0.5-1.0): (0.4-0.6), and the concentration of the carboxymethyl chitosan aqueous solution is 3 wt%.

[0030] Furthermore, in step (3), the mass of glutaraldehyde is 30-50% of the mass of carboxymethyl chitosan.

[0031] Furthermore, in step (3), the pre-freezing process conditions are: pre-freezing in a refrigerator at -10 to -5°C for 12 to 24 hours.

[0032] Furthermore, in step (3), the freeze-drying process conditions are: drying in a freeze dryer at -50 to -45°C for 12 to 24 hours.

[0033] Furthermore, the active admixture is compounded by 5 to 10 parts of metakaolin and 10 to 15 parts of fly ash.

[0034] Furthermore, the foaming agent is an animal protein foaming agent.

[0035] Furthermore, the modifier is prepared by compounding gluconic acid, hydroxyethylidene diphosphonic acid and sodium malate in a mass ratio of 1: (0.3-0.5): (0.3-0.5).

[0036] Furthermore, in step S2, the process conditions of the primary curing and the secondary curing are: placing in an indoor environment with a temperature of 25-35°C and a relative humidity of 60-70% for 20-24 hours, and demolding; then secondary curing for 7-14 days in an indoor environment with a temperature of 20-30°C and a relative humidity of 70-80%, and demolding.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. A fireproof composite board based on magnesium oxysulfide and a preparation method thereof of the present invention comprises the following steps: the carboxyl group of thioglycolic acid is subjected to an amidation reaction with the amino group of melamine to obtain modified melamine; then a -Cl in phenylphosphoryl dichloride is reacted with a hydroxyl group in 4-hydroxyphenylboric acid to obtain an intermediate; finally, the remaining -Cl in phenylphosphoryl dichloride is reacted with an amino group in the modified melamine to obtain a flame retardant containing N, P, and B elements, and containing both thiol and amino groups, thereby providing active sites for subsequent reactions;

[0039] Oleylamine with aliphatic long chains is grafted onto graphene oxide to introduce double bonds, which improves the hydrophobicity of graphene oxide, makes graphene oxide less likely to agglomerate, and improves the dispersibility of graphene oxide. Flame retardants are then used to undergo thiol-ene click reaction with graphene oxide containing double bonds, which further improves the flame retardant properties of graphene oxide. At the same time, amino groups are introduced to enable them to undergo cross-linking reaction with the aldehyde groups of glutaraldehyde, thereby achieving chemical cross-linking of graphene oxide sheets and polymer groups, thereby improving the hydrophobicity and fire retardancy of the aerogel.

[0040] 2. A fireproof composite board based on magnesium oxysulfide and a preparation method thereof of the present invention, carboxymethyl chitosan as a natural polymer material, has excellent biocompatibility and environmental protection characteristics; modified graphene oxide is used as a flame retardant, which can effectively improve the fireproof performance of the material; nanocellulose is used as a reinforcing material, which further improves the strength and toughness of the composite material; at the same time, hydroxyapatite nanowires with good flexibility are used as the skeleton of the aerogel to ensure the lightweight characteristics and excellent thermal insulation performance of the composite material; glutaraldehyde is used as a cross-linking agent, and after freeze-drying, a composite aerogel is obtained. The composite aerogel prepared by the present invention has excellent properties such as heat insulation, light weight, hydrophobicity, temperature resistance, and fire prevention. It can modify and composite magnesium oxysulfide materials, significantly making up for the defects of existing fireproof boards in terms of poor water resistance, high density, and high thermal conductivity, thereby improving its overall performance and application value. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] In this embodiment, light-burned magnesium oxide: average particle size is 200 mesh, magnesium oxide content is 92%, sourced from Hebei Meishen Technology Co., Ltd.; magnesium sulfate: magnesium sulfate content is ≥98%, sourced from Zhejiang Huaxuan Chemical Co., Ltd.; graphene oxide: thickness is 1-3nm, diameter is 4-7μm, number of layers is 2-5, sourced from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; nanocellulose: CNF, sourced from Hubei Xinyuhong Biomedical Technology Co., Ltd.; hydroxyapatite nanowire: length is 100-200μm, diameter is 10-100nm, sourced from From Suzhou Kaifa New Materials Technology Co., Ltd.; kaolin: particle size is 1250 mesh, sourced from Shijiazhuang Aihong Mineral Products Co., Ltd.; fly ash: first-grade fly ash, particle size is 200-300 mesh, sourced from Jining Hengzhi New Building Materials Co., Ltd.; foaming agent: animal protein foaming agent, model FP-50; non-woven fabric: PP non-woven fabric, gram weight is 25-60g / ㎡, sourced from Dongying Libangte New Materials Co., Ltd.; alkali-resistant glass fiber mesh cloth: mesh specification is 5 mesh, gram weight is 125g / ㎡, sourced from Anping Quantuo Wire Mesh Products Co., Ltd.

[0043] In the following examples and comparative examples, 1 part is equal to 10 g.

[0044] Embodiment 1: A method for preparing a fireproof composite board based on magnesium oxysulfide, comprising the following process:

[0045] Step S1: Mix 20 parts of light-burned magnesium oxide and 25 parts of magnesium sulfate aqueous solution (density 1.25 g / cm 3 ) are mixed evenly, 0.1 parts of a modifier (gluconic acid, hydroxyethylidene diphosphonic acid and sodium malate are compounded in a mass ratio of 1:0.3:0.3), 5 parts of a composite aerogel, 15 parts of an active admixture (5 parts of metakaolin and 10 parts of fly ash are compounded) and 0.1 parts of a foaming agent are added and mixed evenly to obtain a modified magnesium oxysulfate cement slurry;

[0046] Step S2: laying a layer of non-woven fabric and a layer of alkali-resistant glass fiber mesh cloth on the template in sequence, pouring modified magnesium oxysulfate cement slurry, and then laying a layer of alkali-resistant glass fiber mesh cloth and a layer of non-woven fabric in sequence; performing primary curing and secondary curing (placing for 20 hours in an indoor environment at a temperature of 25° C. and a relative humidity of 60%, and demolding; then performing secondary curing for 7 days in an indoor environment at a temperature of 20° C. and a relative humidity of 70%, and demolding), to obtain a fireproof composite board;

[0047] The preparation method of composite aerogel is as follows:

[0048] Step (1): 100 parts of a 10 mg / mL graphene oxide aqueous solution, 0.12 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.1 parts of N-hydroxysuccinimide are mixed, and ultrasonic treatment is performed for 30 minutes. A mixed solution of 3 parts of oleylamine, 45 parts of ethanol and 30 parts of deionized water is added, and the ultrasonic treatment is continued for 2 hours. The mixture is stirred for 22 hours, and after centrifugation, filtration and drying, graphene oxide containing double bonds is obtained;

[0049] Step (2): 1.8 parts of double-bond graphene oxide, 3.6 parts of flame retardant and 0.54 parts of photoinitiator were mixed evenly, and then irradiated with ultraviolet light (irradiation wavelength 360nm, irradiation time 0.5h, irradiation intensity 20mW / cm 2 ), to obtain modified graphene oxide;

[0050] Step (3): 200 parts of 3 wt% carboxymethyl chitosan aqueous solution, 1.2 parts of modified graphene oxide, 3 parts of nanocellulose, and 2.4 parts of hydroxyapatite nanowires are mixed evenly, ultrasonically treated for 1 hour, 1.8 parts of glutaraldehyde are added and stirred evenly, and allowed to stand for 3 hours to obtain a composite hydrogel; the composite hydrogel is pre-frozen in a refrigerator at -10°C for 12 hours, and dried in a freeze dryer at -50°C for 12 hours to obtain a composite aerogel;

[0051] The preparation method of the flame retardant is as follows:

[0052] Step A: 4 parts of melamine and 26 parts of pyridine are mixed evenly, heated to 40°C, nitrogen is introduced, 2.4 parts of thioglycolic acid and 5.2 parts of dicyclohexylcarbodiimide are added and mixed evenly, the temperature is raised to 60°C, the temperature is kept for reaction for 1 hour, and modified melamine is obtained after filtration, reduced pressure distillation and drying;

[0053] Step B: 6 parts of 4-hydroxyphenylboric acid and 30 parts of tetrahydrofuran were mixed evenly, and 9 parts of phenylphosphoryl dichloride, 0.06 parts of dibutyltin oxide and 4.8 parts of triethylamine were added under ice bath conditions, and the reaction was continued for 2 hours, and the reaction was continued for 8 hours at room temperature, and the intermediate was obtained after precipitation, filtration, washing and drying;

[0054] Step C: Under nitrogen protection, 4 parts of modified melamine, 5.6 parts of intermediate, 20 parts of toluene and 3.2 parts of triethylamine were mixed evenly, reacted at 65° C. for 2 hours, and a flame retardant was obtained after filtering, washing and drying.

[0055] Embodiment 2: A method for preparing a fireproof composite board based on magnesium oxysulfide, comprising the following process:

[0056] Step S1: 35 parts of light-burned magnesium oxide and 40 parts of magnesium sulfate aqueous solution (density 1.25 g / cm 3 ) are mixed evenly, 1.8 parts of a modifier (gluconic acid, hydroxyethylidene diphosphonic acid and sodium malate are compounded in a mass ratio of 1:0.4:0.4), 10 parts of a composite aerogel, 20 parts of an active admixture (7 parts of metakaolin and 13 parts of fly ash are compounded) and 0.3 parts of a foaming agent are added and mixed evenly to obtain a modified magnesium oxysulfate cement slurry;

[0057] Step S2: laying a layer of non-woven fabric and a layer of alkali-resistant glass fiber mesh cloth on the template in sequence, pouring modified magnesium oxysulfate cement slurry, and then laying a layer of alkali-resistant glass fiber mesh cloth and a layer of non-woven fabric in sequence; performing primary curing and secondary curing (placing for 22 hours in an indoor environment at a temperature of 30° C. and a relative humidity of 65%, and demolding; then secondary curing for 10 days in an indoor environment at a temperature of 25° C. and a relative humidity of 75%, and demolding), to obtain a fireproof composite board;

[0058] The preparation method of composite aerogel is as follows:

[0059] Step (1): 100 parts of a 10 mg / mL graphene oxide aqueous solution, 0.14 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.12 parts of N-hydroxysuccinimide are mixed, and ultrasonic treatment is performed for 50 minutes. A mixed solution of 4 parts of oleylamine, 7.2 parts of ethanol and 6 parts of deionized water is added, and the ultrasonic treatment is continued for 2.5 hours. The mixture is stirred for 23 hours, and after centrifugation, filtration and drying, graphene oxide containing double bonds is obtained;

[0060] Step (2): 3 parts of double-bond graphene oxide, 9 parts of flame retardant and 1.2 parts of photoinitiator were mixed evenly and irradiated with ultraviolet light (the process conditions of ultraviolet light irradiation were: irradiation wavelength 380nm, irradiation time 1h, irradiation intensity 30mW / cm 2 ), to obtain modified graphene oxide;

[0061] Step (3): 300 parts of a 3 wt% carboxymethyl chitosan aqueous solution, 2.7 parts of modified graphene oxide, 6 parts of nanocellulose, and 4.5 parts of hydroxyapatite nanowires are mixed evenly, subjected to ultrasonic treatment for 1.5 hours, 3.6 parts of glutaraldehyde are added, stirred evenly, and allowed to stand for 4 hours to obtain a composite hydrogel; the composite hydrogel is pre-frozen in a refrigerator at -6°C for 18 hours, and dried in a freeze dryer at -48°C for 18 hours to obtain a composite aerogel;

[0062] The preparation method of the flame retardant is as follows:

[0063] Step A: 10 parts of melamine and 660 parts of pyridine are mixed evenly, heated to 45°C, nitrogen is introduced, 6.5 parts of thioglycolic acid and 14 parts of dicyclohexylcarbodiimide are added and mixed evenly, the temperature is raised to 65°C, the temperature is kept for reaction for 1.5 hours, and modified melamine is obtained after filtration, reduced pressure distillation and drying;

[0064] Step B: 14.5 parts of 4-hydroxyphenylboric acid and 110 parts of tetrahydrofuran were mixed evenly, and 22 parts of phenylphosphoryl dichloride, 0.3 parts of dibutyltin oxide and 13 parts of triethylamine were added under ice bath conditions, and the reaction was continued for 3 hours, and the reaction was continued at room temperature for 9 hours. After precipitation, filtration, washing and drying, an intermediate was obtained;

[0065] Step C: Under nitrogen protection, 10 parts of modified melamine, 14.5 parts of intermediate, 60 parts of toluene and 9 parts of triethylamine were mixed evenly, reacted at 70° C. for 3 hours, and a flame retardant was obtained after filtering, washing and drying.

[0066] Embodiment 3: A method for preparing a fireproof composite board based on magnesium oxysulfide, comprising the following process:

[0067] Step S1: 45 parts of light-burned magnesium oxide and 25 parts of magnesium sulfate aqueous solution (density 1.25 g / cm 3 ) are mixed evenly, 3.0 parts of a modifier (gluconic acid, hydroxyethylidene diphosphonic acid and sodium malate are compounded in a mass ratio of 1:0.5:0.5), 15 parts of a composite aerogel, 25 parts of an active admixture (10 parts of metakaolin and 15 parts of fly ash are compounded) and 0.5 parts of a foaming agent are added and mixed evenly to obtain a modified magnesium oxysulfate cement slurry;

[0068] Step S2: laying a layer of non-woven fabric and a layer of alkali-resistant glass fiber mesh cloth on the template in sequence, pouring modified magnesium oxysulfate cement slurry, and then laying a layer of alkali-resistant glass fiber mesh cloth and a layer of non-woven fabric in sequence; performing primary curing and secondary curing (placing for 24 hours in an indoor environment at a temperature of 35° C. and a relative humidity of 70%, and demolding; then performing secondary curing for 14 days in an indoor environment at a temperature of 30° C. and a relative humidity of 80%, and demolding), to obtain a fireproof composite board;

[0069] The preparation method of composite aerogel is as follows:

[0070] Step (1): 100 parts of a 10 mg / mL graphene oxide aqueous solution, 0.15 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.12 parts of N-hydroxysuccinimide are mixed, and ultrasonic treatment is performed for 60 minutes. A mixed solution of 5 parts of oleylamine, 100 parts of ethanol and 100 parts of deionized water is added, and ultrasonic treatment is continued for 3 hours. Stirring is performed for 24 hours, and after centrifugation, filtration and drying, graphene oxide containing double bonds is obtained;

[0071] Step (2): 8 parts of double-bond graphene oxide, 32 parts of flame retardant and 4 parts of photoinitiator were mixed evenly, and then irradiated with ultraviolet light (irradiation wavelength 400nm, irradiation time 2.0h, irradiation intensity 35mW / cm 2 ), to obtain modified graphene oxide;

[0072] Step (3): 500 parts of a 3 wt% carboxymethyl chitosan aqueous solution, 7.5 parts of modified graphene oxide, 15 parts of nanocellulose, and 9 parts of hydroxyapatite nanowires are mixed evenly, subjected to ultrasonic treatment for 2 hours, 7.5 parts of glutaraldehyde are added, stirred evenly, and allowed to stand for 5 hours to obtain a composite hydrogel; the composite hydrogel is pre-frozen in a refrigerator at -5°C for 24 hours, and dried in a freeze dryer at -45°C for 24 hours to obtain a composite aerogel;

[0073] The preparation method of the flame retardant is as follows:

[0074] Step A: 32 parts of melamine and 224 parts of pyridine are mixed evenly, heated to 50°C, nitrogen is introduced, 22.4 parts of thioglycolic acid and 48 parts of dicyclohexylcarbodiimide are added and mixed evenly, the temperature is raised to 70°C, the temperature is kept for reaction for 2 hours, and modified melamine is obtained after filtration, reduced pressure distillation and drying;

[0075] Step B: 48 parts of 4-hydroxyphenylboric acid and 480 parts of tetrahydrofuran were mixed evenly, and 76.8 parts of phenylphosphoryl dichloride, 1.44 parts of dibutyltin oxide and 48 parts of triethylamine were added under ice bath conditions, and the reaction was continued for 4 hours at room temperature for 10 hours. After precipitation, filtration, washing and drying, an intermediate was obtained;

[0076] Step C: Under nitrogen protection, 32 parts of modified melamine, 48 parts of intermediate, 224 parts of toluene and 32 parts of triethylamine are mixed evenly, reacted at 75° C. for 4 hours, and a flame retardant is obtained after filtering, washing and drying.

[0077] Comparative Example 1: The modified magnesium oxysulfate cement slurry comprises the following components by weight: 20 parts of light-burned magnesium oxide, 25 parts of magnesium sulfate aqueous solution, 15 parts of active admixture, 0.1 parts of foaming agent, and 0.1 parts of modifier; compared with Example 1, Comparative Example 1 does not add composite aerogel, and other steps and processes are the same as Example 1.

[0078] Comparative Example 2: A method for preparing a fireproof composite board based on magnesium oxysulfide, comprising the following processes:

[0079] Compared with Example 2, the modifier in Comparative Example 2 is prepared by compounding gluconic acid, hydroxyethylidene diphosphonic acid and sodium malate in a mass ratio of 1:2:1, and the other steps are the same as those in Example 2.

[0080] Comparative Example 3: A method for preparing a fireproof composite board based on magnesium oxysulfide, comprising the following processes:

[0081] The preparation method of composite aerogel is as follows:

[0082] 300 parts of 3 wt% carboxymethyl chitosan aqueous solution, 2.7 parts of graphene oxide, 6 parts of nanocellulose, and 4.5 parts of hydroxyapatite nanowires were mixed evenly, ultrasonically treated for 1.5 hours, 3.6 parts of glutaraldehyde were added and stirred evenly, and allowed to stand for 4 hours to obtain a composite hydrogel; the composite hydrogel was pre-frozen in a refrigerator at -6°C for 18 hours and dried in a freeze dryer at -48°C for 18 hours to obtain a composite aerogel;

[0083] Compared with Example 2, in Comparative Example 3, the modified graphene oxide is replaced with graphene oxide of the same mass, and the other steps are the same as those of Example 2.

[0084] Experiment: Take the fireproof composite boards obtained in Examples 1 to 3 and Comparative Examples 1 to 3, prepare samples, test their properties respectively and record the test results:

[0085] The flexural strength and swelling rate were determined according to the standard of JC 688-2006 "Glass Magnesium Flat Plate", with the sample size of 2440mm×1220mm×8mm; the fire rating was determined according to the standard of GB 8624-2012 "Combustion Performance Classification of Building Materials and Products".

[0086] The test results are as follows:

[0087]

[0088] According to the data in the above table, we can clearly draw the following conclusions:

[0089] Compared with Examples 1 to 3, the flexural strength, swelling rate and fire resistance level of the product obtained in Comparative Example 1 are all reduced, indicating that the composite aerogel prepared by the present invention has significant advantages in mechanical properties, water resistance and fire resistance, thereby improving the overall performance of the fireproof composite board.

[0090] Compared with Examples 1 to 3, the flexural strength of the product obtained in Comparative Example 2 is decreased, which indicates that the addition of the modifier in the present invention can significantly improve the flexural strength of magnesium oxysulfate cement, but the effect is affected by the composition ratio.

[0091] Compared with Examples 1 to 3, the flexural strength, swelling rate and fire resistance level of the product obtained in Comparative Example 3 are all reduced. It can be seen that compared with graphene oxide, the modified graphene oxide prepared by the present invention has better flame retardant effect and hydrophobic properties, thereby effectively improving the fire resistance and water resistance of the material.

[0092] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a fireproof composite board based on magnesium oxysulfide, characterized in that: The steps include: Step S1: light-burned magnesium oxide and magnesium sulfate aqueous solution are mixed evenly, and a modifier, a composite aerogel, an active admixture and a foaming agent are added and mixed evenly to obtain a modified magnesium oxysulfate cement slurry; Step S2: laying a layer of non-woven fabric and a layer of alkali-resistant glass fiber mesh cloth on the template in sequence, pouring modified magnesium oxysulfate cement slurry, and then laying a layer of alkali-resistant glass fiber mesh cloth and a layer of non-woven fabric in sequence; performing primary curing and secondary curing to obtain a fireproof composite board; The modified magnesium oxysulfate cement slurry comprises the following components by weight: 20-45 parts of light-burned magnesium oxide, 25-50 parts of magnesium sulfate aqueous solution, 5-15 parts of composite aerogel, 15-25 parts of active admixture, 0.1-0.5 parts of foaming agent, and 0.1-3.0 parts of modifier; The preparation method of the composite aerogel is as follows: Step (1): mixing a graphene oxide aqueous solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, ultrasonically treating for 30 to 60 minutes, adding a mixed solution of oleylamine, ethanol and deionized water, continuing the ultrasonic treatment for 2 to 3 hours, stirring for 22 to 24 hours, centrifuging, filtering and drying to obtain graphene oxide containing double bonds; Step (2): uniformly mixing the double-bond-containing graphene oxide, a flame retardant and a photoinitiator, and irradiating the mixture with ultraviolet light to obtain modified graphene oxide; Step (3): uniformly mixing the carboxymethyl chitosan aqueous solution, modified graphene oxide, nanocellulose and hydroxyapatite nanowires, ultrasonically treating for 1 to 2 hours, adding glutaraldehyde and stirring evenly, and standing for 3 to 5 hours to obtain a composite hydrogel; pre-freezing and freeze-drying the composite hydrogel to obtain a composite aerogel; The preparation method of the flame retardant is as follows: Step A: Mix melamine and pyridine evenly, heat to 40-50° C., introduce nitrogen, add thioglycolic acid and dicyclohexylcarbodiimide and mix evenly, heat to 60-70° C., keep warm for 1-2 hours, filter, distill under reduced pressure, and dry to obtain modified melamine; Step B: 4-hydroxyphenylboronic acid and tetrahydrofuran are mixed evenly, and phenylphosphoryl dichloride, dibutyltin oxide and triethylamine are added under ice bath conditions, and the reaction is continued for 2 to 4 hours, and the reaction is continued for 8 to 10 hours at room temperature, and an intermediate is obtained after precipitation, filtration, washing and drying; Step C: Under nitrogen protection, the modified melamine, the intermediate, toluene and triethylamine are mixed uniformly, reacted at 65-75° C. for 2-4 hours, filtered, washed and dried to obtain a flame retardant; The modifier is prepared by compounding gluconic acid, hydroxyethylidene diphosphonic acid and sodium malate in a mass ratio of 1: (0.5-1.0): (0.3-0.5).

2. The method for preparing a fireproof composite board based on magnesium oxysulfide according to claim 1, characterized in that: The magnesium sulfate aqueous solution has a density of 1.2 to 1.3 g / cm 3 of magnesium sulfate aqueous solution.

3. The method for preparing a fireproof composite board based on magnesium oxysulfide according to claim 1, characterized in that: In the step (2), the mass ratio of the double-bond graphene oxide, the flame retardant and the photoinitiator is 1: (2-4): (0.3-0.5).

4. The method for preparing a fireproof composite board based on magnesium oxysulfide according to claim 1, characterized in that: In the step (3), the mass ratio of carboxymethyl chitosan, modified graphene oxide, nanocellulose and hydroxyapatite nanowires is 1: (0.3-0.5): (0.5-1.0): (0.5-1.0), and the concentration of the carboxymethyl chitosan aqueous solution is 3 wt%.

5. The method for preparing a fireproof composite board based on magnesium oxysulfide according to claim 1, characterized in that: The active admixture is compounded by 5 to 10 parts of metakaolin and 10 to 15 parts of fly ash.

6. A fireproof composite board based on magnesium oxysulfide obtained according to the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Integration board for decorating, preventing fire and keeping warm

    CN104563425A

  • Aerogel modified magnesium oxysulfate fireproof insulation board and preparation method thereof

    CN113979715A